Design of Temperature Measurement System on The Drying Process of Madura Tobacco Leaves - Wardana, Humadillah Kurniadi; Endarko, Endarko (Institut Teknologi Sepuluh Nopember, 2015)
The quality of dried chopped leaves of tobacco is an important factor. The present work developed an oven for drying process to measure and evalute on drying shrinkage characteristic of choped leaves Madura tobacco. The oven has three racks for analyzing and monitoring the rate of drying shrinkage of Madura tobacco. Every rack has a different amount of chopped leaves as follows: 120 g on top rack, 100 g for middle rack and 80 g for bottom rack. Rate of drying shrinkage was analyzed for 20 minutes. The results showed that every rack has different rate of drying shrinkage for drying time. The rate of drying shrinkage was achieved at 26-35% for all racks with temperature distribution in oven at 25 – 30 C.